Catalytic Materials: Continuous Synthesis of Hollow High‐Entropy Nanoparticles for Energy and Catalysis Applications (Adv. Mater. 46/2020). Issue 46 (17th November 2020) - Wang, Xizheng; Dong, Qi; Qiao, Haiyu; Huang, Zhennan; Saray, Mahmoud Tamadoni; Zhong, Geng; Lin, Zhiwei; Cui, Mingjin; Brozena, Alexandra; Hong, Min; Xia, Qinqin; Gao, Jinlong; et al.
Abstract : Combining multiple precious‐ and nonprecious‐metal elements in a hollow high‐entropy alloy (HEA) structure as catalysts can efficiently improve the usage of active sites, enhance activity, and achieve high stability. In article number 2002853, Liangbing Hu and co‐workers report a rapid and continuous high‐temperature nanomanufacturing method for hollow HEA nanoparticles through a "droplet‐to‐particle" transformation.